The moderating role of gender and generation in the impact of destination image on behavioural intention at world natural heritage site - Zheng, Qiwen; Rahman, Suraiyati (Journal of Tourism Management Research, 2025)
This study examines the links between cognitive image (COG), affective image (AF), and CON, as well as the relationship between DI and behavioral intentions (BI) across gender and generational groups. Data from 388 valid responses collected at Mount Sanqingshan National Park were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA). The findings underscore the pivotal role of COG within the DI construct, indirectly influencing BI through AF and CON. It also finds that CON has a significant direct impact on BI. Gender analysis reveals highly substantial differences in the effects of COG on AF, COG on BI, and AF and BI across female and male tourists. Generationally, there is a considerable difference between the post-2000s/1990s and post-1980s/1970s groups regarding the relationship between COG and BI, COG and CON, and AF and CON. This research represents the first attempt to evaluate the inner association (including CON) and its relationships with BI, while also considering gender and generation to determine whether these factors moderate these elements. These insights enhance the understanding and management of tourist perceptions and behaviors towards WNHSs, providing practical guidance for improving WNHSs’ strategies for diverse tourist groups.